Analisis Faktor-Faktor Resiko yang Berhubungan Dengan Kejadian TB.Paru di Puskesmas Kertapati Palembang Tahun 2017 - Sucipto (IKEMAS: Jurnal Ilmu Kesehatan Masyarakat, 2018)
Tuberculosis (TB) is a contagious disease directly caused by the bacteria Mycobacterium tuberculosis. Tuberculosis is still a global health problem and is the second leading cause of death after HIV. WHO estimates that in 2011 there were 8.7 million new cases of tuberculosis (13% were co-infected with HIV) and 1.4 million people died from tuberculosis (WHO, 2012). This study aims to determine the analysis of factors associated with Risk of Pulmonary Tuberculosis at Puskesmas Kertapati Palembang City Year 2017. The research design was conducted by qualitative descriptive research method supported by analytical survey with cross-sectional survey design. Sampling technique sampling total 35 respondents at Puskesmas Kertapati Palembang, South Sumatera Province in 2017, this research was conducted on 30 June until 10 July 2017. Multiple regression logistic analysis showed that there was a significant correlation between humidity (p value 0,034) and smoking behavior (p value 0,053) with pulmonary TB incidence at Puskesmas Kertapati Palembang City 2017. Suggestions in this study is prevention by providing information or counseling to the community how prevention of pulmonary tuberculosis in the working area of Puskesmas Kertapati Palembang.